Implementation of Search Engine Optimization (SEO) with RankMath Plugin to Increase WordPress-Based Website Visits - Ghazali, Ghazali; Isnain, Auliya Rahma (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
Search Engine Optimization (SEO) is a series of processes carried out systematically on a website to increase visitor traffic through search engines. SEO needs to be applied to websites with the aim of being indexed by search engines. It is known that one of the CV. Alfiel Elektronik companies in Bandar Lampung has used a website in marketing its products. However, the website is not indexed in the Google Search Engine, so there are no visitors. In order for the website to be indexed and appear on the top page of Google search, the solution is to apply the SEO Method, namely On-Page SEO (inside the website) and Off-Page SEO (outside the website). SEO requires quite high knowledge and skills, and requires a lot of time and money. Therefore, tools are needed that can simplify and speed up the SEO process. One of the tools used is the RankMath plugin. RankMath is an SEO plugin that provides complete features and is easy to use to optimize WordPress websites. The purpose of this research is to apply the SEO Method with the RankMath plugin to increase website visits. The website is measured for SEO performance before and after using the RankMath plugin. The methods used in SEO optimization in this research are planning, analysis, design, implementation, testing and maintenance. The implementation of SEO is able to increase the ranking of the Alfiel Electronic website with the domain, https://alfiel-electronic.com/, increase the SEO audit value on Ahrefs and increase the number of visits and website page impressions. This shows that the RankMath plugin is effective for improving SEO and website visits.